The spatial pattern of Populus euphratica competition based on competitive exclusion theory - Liu, Yaxuan; Zeng, Yong; Wang, Peng; He, Jia; Li, Pingping; Liang, Yuejia (Frontiers in Plant Science, 2024)
Introduction Population-level competition and spatial patterns may explain the role of competitive exclusion in communities, which is important for vegetation restoration and biodiversity conservation. Methods We analyzed the competitive intensity, spatial patterns, and renewal of Populus euphratica Oliv. forests in the Tarim River Basin using the Hegyi competition index and spatial point pattern analysis in a completely random model with different habitats and different forest ages. Results The greatest competitive distance for P. euphratica was 10 m, and the intensity of competition steadily decreased as the diameter increased. The intensity of intraspecific and interspecific competition in young, mature, and old P. euphratica forests was as follows: riverside habitat > transitional habitat > desert margin habitat. The Simpson index values for the three habitats decreased as follows: transitional > riverside > desert margin, and the Shannon-Wiener index and Pielou index values decreased as follows: riverside > transitional > desert margin. In the riverside habitat, the young P. euphratica forest experienced the greatest competitive intensity, the mature forest in the transitional habitat was the largest, and the forest in the desert margin habitat was the oldest. Competitive intensity was greatest in the young riverside P. euphratica forest, mature P. euphratica forest in the transitional habitat, and old forest in the desert margin. Riverside P. euphratica experienced strong competition from Populus pruinosa. Competitive exclusion caused P. pruinosa to disappear from the transitional and desert margin habitats. Young, mature, and old P. euphratica forests were randomly distributed along the riverside and in the transitional habitat, while mature and old P. euphratica forests were randomly distributed in the desert margin. Populus pruinosa, Tamarix ramosissima, and Tamarix hispida were mainly randomly distributed, and T. ramosissima and T. hispida were clustered at small scales. In the riverside habitat, young, mature, and old P. euphratica had no spatial correlation, and there was a significant negative correlation at small scales in the transitional habitat. The density of P. euphratica seedlings in the riverside habitat was greater than that in the transitional habitat, and greater competitive pressures on P. euphratica tree seedlings caused a lower renewal density. Conclusions When planting P. euphratica forests, spacing greater than 10 m can effectively reduce stand competition and thus promote seedling regeneration.